2011
DOI: 10.1002/app.34154
|View full text |Cite
|
Sign up to set email alerts
|

Greatly improved adsorption of N‐methylated modified macroporous cross‐linked polyacrylamide toward tannin from aqueous solution

Abstract: Macroporous cross-linked poly(N-methylacrylamide) (PMAM) was prepared and the adsorption behaviors of PMAM toward tannin from aqueous solution was studied in comparison with polyacrylamide (PAM). The swollen property indicated that PMAM had a higher hydrophobicity than PAM while the adsorption showed that PMAM had a greatly improved adsorption toward tannin. The adsorption data could be fitted well by Freundlich model and the values of the thermodynamic parameters of PMAM toward tannin were more negative than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Another work indicated that the hydrophobic interaction and multiple hydrogen bonding between poly( N -methyl acrylamide) (PMAM)/polyacrylamide (PAM) and tannin were responsible for stabilizing these composites. 186 Due to the hydrogen bonding and good hydrophobicity of PMAM, it was easier to form a PMAM–tannin composite rather than PAM–tannin.…”
Section: Design Of Tannin-immobilized Composites Using Various Substr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another work indicated that the hydrophobic interaction and multiple hydrogen bonding between poly( N -methyl acrylamide) (PMAM)/polyacrylamide (PAM) and tannin were responsible for stabilizing these composites. 186 Due to the hydrogen bonding and good hydrophobicity of PMAM, it was easier to form a PMAM–tannin composite rather than PAM–tannin.…”
Section: Design Of Tannin-immobilized Composites Using Various Substr...mentioning
confidence: 99%
“…185 3.2.6 Other synthetic polymers. Moreover, other synthetic polymers, such as polyamide (PAM), 17,186 polyethylene glycol (PEG), [187][188][189] polyacrylonitriles (PAN), 190 and polypyrroles (Ppy), 191 were also used as substrates for the immobilization of tannins and their derivatives.…”
Section: Polyvinylidene Fluoride (Pvdf)mentioning
confidence: 99%